ANALISIS PDRB, UPAH MINIMUM KABUPATEN, DAN PENDIDIKAN TERHADAP KESEMPATAN KERJA DI PROVINSI JAWA TIMUR - Nanik Istiyani; Sebastiana Viphindrartin; Budi Nurhardj; A I Restiawan (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
This study aims to examine the effect of Gross Domestic Product, District Minimum Wage, and Education on Employment Opportunities in East Java. This type of research is explanatory research which is a research that aims to determine the effect of the variable product influence Gross Regional Domestic, Minimum Wage, and Education on Employment Opportunities in East Java. The method used in this study is panel data with a Fixed Effect approach and is associated with descriptive analysis. Based on the results of the study, it shows that the Gross Regional Domestic Product variable has a positive and significant effect on Employment Opportunities in East Java, the Regency Minimum Wage has a negative and significant effect on Employment Opportunities in East Java and Education has a positive and significant effect on Employment Opportunities in East Java